Combustion and Emission Analysis of Various Gaseous Fuels in Spark Ignition Engine using MATLAB Simulation - Giri, Subrat; Rana, Asmi; Nagarkoti, Anup; Luintel, Mahesh; Adhikari, Surya Prasad (Journal of Advanced College of Engineering and Management, 2025)
In this research Hydrogen, Syngas and Compressed natural gas were used to simulate a spark-ignition engine using MATLAB and Simulink. Here, the combustion and emission of the engine using hydrogen, syngas (mixture of carbon monoxide (CO) and hydrogen (H2)) and compressed natural gas were analyzed considering various engine parameters and compared the obtained results with gasoline. The simulation's results were used to describe the physical processes in the combustion chamber, which determine engine power and emission under various operating situations. The performance of each fuel in a spark ignition engine under the same operating conditions, such as equivalency ratio, rpm, compression ratio, and spark timing were compared. The obtained results showed that the hydrogen and syngas can be run in both lean and rich condition, which helps to reduce fuel consumption, whereas gasoline and natural gas can run only at a stoichiometric air-fuel ratio.